2020
DOI: 10.14814/phy2.14334
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperoxia exposure induces aortic biomechanical alterations and cardiac dysfunction in juvenile rats

Abstract: Supplemental oxygen (O 2 ) therapy in preterm infants impairs lung development, but the impact of O 2 on long-term systemic vascular structure and function has not been well-explored. The present study tested the hypothesis that neonatal O 2 therapy induces long-term structural and functional alterations in the systemic vasculature, resulting in vascular stiffness observed in children and young adults born preterm.Newborn Sprague-Dawley rats were exposed to normoxia (21% O 2 ) or hyperoxia (85% O 2 ) for 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Still, larger vessels in these animals exhibit remodeling characterized by augmented collagen deposition, and reduced elastin ( Walton et al, 2016 ). Similar observations were made in rat aortas, along with cardiac remodeling ( Benny et al, 2020 ). IUGR also favors arterial remodeling in the adult offspring, as observed in sheep ( Dodson et al, 2014 ).…”
Section: Maternal Stress and Fetal Programming Of Cardiovascular Dysf...supporting
confidence: 82%
“…Still, larger vessels in these animals exhibit remodeling characterized by augmented collagen deposition, and reduced elastin ( Walton et al, 2016 ). Similar observations were made in rat aortas, along with cardiac remodeling ( Benny et al, 2020 ). IUGR also favors arterial remodeling in the adult offspring, as observed in sheep ( Dodson et al, 2014 ).…”
Section: Maternal Stress and Fetal Programming Of Cardiovascular Dysf...supporting
confidence: 82%
“… 38 Disruption of elastin synthesis at the end of gestation or with preterm birth may increase arterial stiffness as supported by experimental models. 39 , 40 Desmosine levels—an elastin breakdown product—were also elevated in a cohort of young adults born extremely preterm, though they did not correlate with PWV or augmentation index. 41 Boardman et al 34 performed a detailed study of major systemic arteries in 102 young adults born very preterm at an average of 30 weeks’ gestation compared with 102 term-born age-matched controls.…”
Section: Late Sequelae and Future Cardiovascular Disease Riskmentioning
confidence: 89%
“…11,12,14 When birth is preterm, an immature myocardium must undertake the transition. Clinical [3][4][5][6][7] and experimental 8,9,15,37 studies have demonstrated morphological and functional cardiac alterations in adults born preterm, as well as in animal models 37,38 simulating conditions associated with preterm birth. However, mechanisms of cardiac alterations after preterm birth are not well known.…”
Section: Discussionmentioning
confidence: 99%